ROLE-PLAYING MODEL: IS IT EFFECTIVE TO IMPROVE STUDENTS’ ACCOUNTING LEARNING MOTIVATION AND LEARNING ACHIEVEMENTS? - Laurentius Saptono; Budi Eko Soetjipto; Wahjoedi Wahjoedi; Hari Wahyono (LPMPP Universitas Negeri Yogyakarta, 2020)
Teachers need to organize learning that is contextual, innovative, and interesting so that students are more motivated to learn and they get better learning outcomes. The research was aimed to examine the effectiveness of role-playing model to improve the twelfth-grade social students’ learning motivation and their learning achievements on accounting subject with basic competence of practicing accounting cycles of service companies. The research was conducted with a quasi experiment for 3 public high schools in Sleman Regency. There were 206 total respondents for this research. Research data was gathered by using two methods: tests and questionnaires. Independent sample t-test was used for data analysis techniques. The result of this research showed that t-test for equality of mean of learning motivation was significant (sig. = .000 α = .05) and learning achievement was also significant (sig. = .000 α = .05). At the treatment class, students’ learning motivation was very high and their learning achievement was high. Thus, it was concluded that the role playing model was effective to improve the twelfth-grade social students’ learning motivation and their learning achievements on accounting subject with basic competence of practicing accounting cycles of service companies.